Analisis Tingkat Kesiapan Siswa Terhadap Proses Pembelajaran Berbasis AI di SMK Negeri 2 Salatiga - Salemban, Rica; Krismiyati, Krismiyati (Jurnal Ilmu Komputer dan Informatika, 2025)
The rapid advancement of Artificial Intelligence (AI) challenges vocational education to ensure students are ready for technology-based learning. Yet, the level of readiness among vocational high school students remains underexplored. This research analyzes the readiness of students at SMK Negeri 2 Salatiga to engage in AI-based learning using the Technology Readiness Index (TRI) 2.0 framework. A total of 63 eleventh-grade Computer and Network Engineering students completed a structured questionnaire. Data were examined through descriptive statistics with validity and reliability tests to confirm instrument accuracy. Findings reveal an overall TRI score of 2.44, indicating a moderate level of readiness. Among the four TRI dimensions, optimism recorded the highest mean (2.93), reflecting students’ positive outlook toward AI benefits, while insecurity showed the lowest mean (2.13), highlighting concerns over security and dependability. These results underscore the importance of educational strategies that enhance not only technical competence but also students’ confidence and sense of safety when using AI. The study enriches the discourse on AI readiness in vocational education and provides a foundation for curriculum improvements and AI-oriented training programs that better equip students for the digital era.